The distribution of the islets of Langerhans in pancreas of euglycemic spontaneously hypertensive rats - T. V. Abramova (Zaporozhye State Medical University, 2016)
Considering the fact, that pancreatic beta cells are responsible for production of all insulin needed to maintain the glucose homeostasis, the problem of beta cells pull control in patients with hypertension is rather topical. It cannot be ruled, that genetical defects of congenital hypertension formation can affect the mechanisms of maintaining of the cell mass of pancreatic endocrinocytes and lead to violation of glucose metabolism and diabetes mellitus development. Moreover, the violation of cytoarchitectonics of pancreatic islets of Langerhans may lead to impairment of the insulin secretion, which can be due to local impairment of the blood circulation in patients with hypertension. The aim was to study the features of SHR islets' distribution in pancreas. Materials and methods. The glucose blood level and the insulin concentration were measured from tail vein. The immunofluorescence analysis was made and data were processed with statistical application kit with evaluation of reliability of differences in experimental groups with Student's t-criterion. Results. The object of current study was the animals with fasting normoglycemia and Wistar rats with 3.94 mmol/l fasting glucose level. The morphometrical assay showed 78.8% of pancreatic islets in SHR are small islets, while in Wistar rats their share is 44.3%. Noteworthy is the great amount of solely beta-cells in SHR and total absence of large islets. Conclusions. The violation of pancreas' cytoarchitectonic and changes of islets' distribution with prevailing of small islets with area less than 1500 µm2 were observed. Beta-cells in normoglycemic SHR were characterized with 2-fold increased concentration of immunoreactive insulin compared with normotensive Wistar rats.